Changes in Efficiency and Quality of Nursing Electronic Health Record Documentation After Implementation of an Admission Patient History Essential Data Set. Issue 5 (May 2019) - Karp, Eva L.; Freeman, Rebecca; Simpson, Kit N.; Simpson, Annie N.
Abstract : The objective of this quality improvement study was to evaluate whether electronic health record system timers and event logs can measure the efficiency and quality of a clinical process in an electronic health record. Using an experimental pre– and post–nonrandomized prospective cohort design, the researchers introduced a newly defined admission patient history essential data set and examined the electronic health record event files and timers to analyze the nursing experience from an efficiency and quality perspective. The researchers evaluated efficiency by measuring the time and clicks required to complete an admission history. The average active time spent documenting the admission patient history decreased by 72% from the preintervention measure (mean = 9.30 minutes) to the postintervention measure (mean = 2.55 minutes). The number of clicks decreased by 76% from the preintervention number of clicks (mean = 151.5) to the postintervention number of clicks (mean = 35.93). The quality of documentation was measured as the proportion of completed essential items and the frequency of completing an assessment in one sequence. The capture of essential data elements improved by almost 6%, and admission patient history data completed in one sequence increased by 24%. These study results demonstrate that system timers and event logs can measure the preintervention and postintervention changes in efficiency and quality of a defined clinical workflow into an electronic health record.